Show that y=x+tanx satisfies the differential equation cos2x d2y /dx2 -2y+2x=0
Given, "y=x+\\tan x ...(i)"
On differentiating both sides w.r.t "x" ,
"\\frac{dy}{dx}=1+\\sec ^2x"
Again, differentiating both sides w.r.t "x" ,
"\\frac{d^2y}{dx^2}=0+2\\sec x \\frac{d (\\sec x)}{dx}=2\\sec x \\sec x\\tan x\n\\\\\\Rightarrow \\frac{d^2y}{dx^2}=2\\sec^2 x \\tan x ...(ii)"
Now, differential equation is: "\\cos ^2x \\frac{d^2y}{dx^2}-2y+2x=0"
Put values from equation (i) and (ii) into LHS of this, we get:
"=\\cos ^2x (2\\sec^2 x \\tan x)-2(x+\\tan x)+2x"
"=\\cos ^2x (2 \\times\\frac{1}{\\cos ^2x} \\tan x)-2x-2\\tan x+2x \\ [\\because \\ \\sec x=\\frac{1}{\\cos x}]\n\\\\ =2 \\tan x-2x-2\\tan x+2x\n\\\\ =0+0\n\\\\ =0\n\\\\ =RHS"
Hence, proved.
Comments
Leave a comment